Deletion and methylation of the tumour suppressor gene p16/CDKN2 in primary head and neck squamous cell carcinoma. Issue 6 (June 1997) - González, M V; Pello, M F; López-Larrea, C; Suárez, C; Menéndez, M J; Coto, E
Abstract : AIMS: To study the homozygous deletion and methylation status of the 5' CpG island of the p16 and p15 genes (9p21) in a set of primary advanced head and neck squamous cell carcinomas (SCC) and to test whether inactivation of these genes by these mechanisms contributes to head and neck SCC development. METHODS: DNA was extracted from fresh tumours. Homozygous deletion was determined by the polymerase chain reaction (PCR) followed by hybridisation with the corresponding probe, radioactively labelled by the random priming method. Methylation status of the CpG island of the 5' region of these genes was assessed by digestion with the appropriate restriction enzymes followed by PCR and subsequent hybridisation with the corresponding probe. The presence of point mutations was determined by PCR-SSCP (single strand conformation polymorphism). RESULTS: The p16 and p15 genes were homozygously deleted in 20% and 10% of the tumours, respectively. No point mutations were found at p16 and p15. The 5' CpG island at the p16 gene was methylated in 20% of the cases. CONCLUSIONS: The tumour suppressor gene p16 is inactivated through homozygous deletion or methylation in a significant proportion of cases of head and neck SCC.